Efeitos imunomoduladores de uma linhagem de Lactococcus lactis invasiva e produtora do antígeno Hsp65 de Mycobacterium leprae em modelos murinos de colite aguda e crônica induzidas pelo ácido trinitrobenzeno sulfônico (TNBS) - Vanessa Pecini da Cunha (2020)
Inflammatory bowel diseases (IBDs) are a set of disorders that affect the gastrointestinal tract. IBDs essentially comprise two diseases, Crohn’s disease (CD) and ulcerative colitis (UC), which are characterized by chronic and recurrent inflammation of the mucosa. In addition, one of the main complications of CD is the development of fibrosis, which results from excessive accumulation of collagen in the intestine layers. The treatment is usually performed with anti-inflammatory drugs, immunosuppressants, antibiotics, biological drugs and surgery, but these treatments are linked to several adverse effects. In view of this problem, there is a need to develop more effective treatments for patients with CD. Thus, heat shock proteins (HSPs) might serve as an alternative treatment because these antigens play important roles in the regulation of effector T cells. Therefore, the present study aimed to evaluate the immunomodulatory potential of the invasive and Hsp65-producing strain [L. lactis NCDO2118 FnBPA+ (pXYCYT:Hsp65)] in murine models of acute and chronic colitis as an alternative therapeutic strategy against experimental CD. For this, the pXYCYT:Hsp65 plasmid was transformed into the L. lactis NCDO2118 FnBPA+ strain, resulting in the L. lactis NCDO2118 FnBPA+ (pXYCYT:Hsp65) strain. Then, the functionality of the strain was evaluated in vitro for Hsp65 production by Western blotting and for invasion into Caco-2 cells. The results demonstrated that the strain was able to produce Hsp65 and efficiently invade eukaryotic cells. Subsequently, in vivo, experimental colitis was induced by trinitrobenzene sulfonic acid (TNBS) in BALB/c mice, and the mice were treated orally with L. lactis NCDO2118 FnBPA+ (pXYCYT:Hsp65) via intragastric gavage. Oral administration of the recombinant strain was able to attenuated the severity of acute colitis by mainly reducing IL-12 and IL-17 levels and increasing IL-10 and sIgA levels. Next, this strain was also able ameliorated chronic colitis (inflammation and fibrosis) through regulation of the pro-fibrotic cytokines IL-13 and TGF-β and the regulatory cytokine IL-10. Finally, this work describes an innovative and promising approach for alternative treatment of experimental CD using mucosal immunity and immunomodulation to restore the intestinal homeostasis of this IBD.